Pengaruh Model Kooperatif Tipe Picture and Picture Berbantuan Media Flashcard untuk Meningkatkan Keterampilan Membaca Permulaan di SDN 235 Lengkong Kecil (Penelitian Quasi-Experimental pada Peserta Didik Kelas I SDN 235 Lengkong Kecil) - Suci Insan Sapitri; Azis Lukman Praja; Arifin Ahmad (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Early reading skills are a fundamental competency that supports students’ success in subsequent learning. However, many first-grade elementary school students still experience difficulties in recognizing letters, reading syllables, words, and simple sentences due to the use of less varied learning models and limited instructional media. This study was motivated by the low early reading skills of first-grade students at SDN 235 Lengkong Kecil, Bandung. The study aimed to determine the effect of the Picture and Picture cooperative learning model aided by flashcards on students’ early reading skills. This research employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The sampling technique used was saturated sampling, involving 56 students, consisting of Class 1A as the experimental group and Class 1B as the control group. The findings indicated that early reading skills improved in both groups. The experimental group’s mean score increased from 36.78 in the pretest to 80.67 in the posttest, with an average N-Gain score of 0.6907 (moderate category). Meanwhile, the control group’s mean score increased from 43.00 to 70.92, with an average N-Gain score of 0.4864 (moderate category). Hypothesis testing using an independent samples t-test revealed a significant difference, with a Sig. (2-tailed) value of < 0.001 (< 0.05). These findings indicate that the Picture and Picture cooperative learning model aided by flashcards has a significant positive effect on improving the early reading skills of first-grade students at SDN 235 Lengkong Kecil, Bandung.